THE ROLE OF PROFITABILITY IN MODERATING THE RELATIONSHIP BETWEEN LEVERAGE AND COMPANY SIZE ON ENVIRONMENTAL PERFORMANCE - Puspita, Dyah Aruning; Cindy Vanessa Saputra; Sugeng Hariadi (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
The purpose of this study is to examine the effect of leverage and company size on environmental performance, moderated by profitability. This study used a purposive sampling method, taking samples from raw material sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The sample consisted of 30 companies, yielding 90 secondary data points. The analysis method employed in this research was PLS-SEM, including descriptive statistical analysis and path coefficient analysis, tested using SmartPLS 4.0. The study's results indicate that leverage significantly affects environmental performance, and company size significantly affects environmental performance. However, profitability does not moderate the influence of leverage on environmental performance, nor does it moderate the influence of company size on environmental performance.